2003
DOI: 10.3989/cyv.2003.v42.i2.643
|View full text |Cite
|
Sign up to set email alerts
|

Desarrollo de un cemento de base silicatada a partir de rocas volcánicas vítreas alcalinas: interpretación de los resultados preindustriales basada en la composición químico-mineralógica de los precursores geológicos

Abstract: Desarrollo de un cemento de base silicatada a partir de rocas volcánicas vítreas alcalinas: interpretación de los resultados preindustriales basada en la composición químico-mineralógica de los precursores geológicos D.GIMENO (1) , J.DAVIDOVITS (2) , C.MARINI (3) , P.ROCHER (4) , S.TOCCO (4) , S.CARA (4) , N.DIAZ (1) , C.SEGURA (1) , G.SISTU (6) (1) Dept. Geoquímica, Petrologia i Prospecció Geològica, Fac. Geologia, Universitat de Barcelona, 08028 -Barcelona. Domingo@natura.geo.ub.es (2) El proye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…They used this diatomaceous earth for the production of lightweight bricks and analysed their pozzolanic behaviour. The authors observed that calcination temperature of 700°C led to dehydroxylation of kaolinite (Le Chatelier, 1887; Jeffries, 1944; Frost and Vassallo, 1996; Fernandez et al , 2011); it resulted in the collapse of the clay minerals structures as confirmed by the disappearance of clay minerals peaks in the XRD spectra, and relative change of the coordination state of Si and Al atoms as traced by NMR (Sanz et al , 1988; Chandrasekhar, 1996; Gimeno et al , 2003; Drits et al , 2016).…”
Section: Resultsmentioning
confidence: 99%
“…They used this diatomaceous earth for the production of lightweight bricks and analysed their pozzolanic behaviour. The authors observed that calcination temperature of 700°C led to dehydroxylation of kaolinite (Le Chatelier, 1887; Jeffries, 1944; Frost and Vassallo, 1996; Fernandez et al , 2011); it resulted in the collapse of the clay minerals structures as confirmed by the disappearance of clay minerals peaks in the XRD spectra, and relative change of the coordination state of Si and Al atoms as traced by NMR (Sanz et al , 1988; Chandrasekhar, 1996; Gimeno et al , 2003; Drits et al , 2016).…”
Section: Resultsmentioning
confidence: 99%
“…A recent work has evaluated the use of ignimbrite powder in reactive powder concrete road pavement, showing the many possibilities of this material for construction [27]. Ignimbrite, as well as other pyroclastic vitreous volcanic rocks extracted directly from mining prospects, was previously studied for the realization of geopolymeric materials [28]. To our knowledge, there is no literature that studies the properties of geopolymers prepared from ignimbrite rocks from the Arequipa region in Peru.…”
Section: Introductionmentioning
confidence: 99%
“…This suitability is not rare, if we take into account the pore size of these zeolites and the molecular dimension of ammonia [40,41]. In Italy, the zeolitite rocks correspond to a large number of pyroclastic volcanic units mainly related to the potassic alkaline province that are mined for building purposes at great scale since Etruscan and Roman times till today (see in example [42][43][44] and references therein). Italian zeolite suppliers recycle sawing waste of dimension stone blocks for the quarries; and Italian researchers have prospected since 60's of XX century industrial uses of these zeolitites.…”
Section: Introductionmentioning
confidence: 99%